Years of Able Life in Older Persons—The Role of Cardiovascular Imaging and Biomarkers: The Cardiovascular Health Study. Issue 4 (23rd April 2015) - Alshawabkeh, Laith I.; Yee, Laura M.; Gardin, Julius M.; Gottdiener, John S.; Odden, Michelle C.; Bartz, Traci M.; Arnold, Alice M.; Mukamal, Kenneth J.; Wallace, Robert B.
Abstract : Background: As the U.S. population grows older, there is greater need to examine physical independence. Previous studies have assessed risk factors in relation to either disability or mortality, but an outcome that combines both is still needed. Methods and Results: The Cardiovascular Health Study is a population‐based, prospective study where participants underwent baseline echocardiogram, measurement of carotid intima‐media thickness (IMT), and various biomarkers, then followed for up to 18 years. Years of able life (YAL) constituted the number of years the participant was able to perform all activities of daily living. Linear regression was used to model the relationship between selected measures and outcomes, adjusted for confounding variables. Among 4902 participants, mean age was 72.6±5.4 years, median YAL for males was 8.8 (interquartile range [IQR], 4.3 to 13.8) and 10.3 (IQR, 5.8 to 15.8) for females. Reductions in YAL in the fully adjusted model for females and males, respectively, were: −1.34 (95% confidence interval [CI], −2.18, −0.49) and −1.41 (95% CI, −2.03, −0.8) for abnormal left ventricular (LV) ejection fraction, −0.5 (95% CI, −0.78, −0.22) and −0.62 (95% CI, −0.87, −0.36) per SD increase in LV mass, −0.5 (95% CI, −0.7, −0.29) and −0.79 (95% CI, −0.99, −0.58) for IMT, −0.5 (95% CI, −0.64, −0.37) and −0.79 (95% CI, −0.94, −0.65) for N‐terminal pro‐brain natriuretic peptide, −1.08 (95% CI, −1.34, −0.83) and −0.73 (95% CI, −0.97, −0.5) for high‐sensitivity troponin‐T, and −0.26 (95% CI, −0.42, −0.09) and −0.23 (95% CI, −0.41, −0.05) for procollagen‐III N‐terminal propeptide. Most tested variables remained significant even after adjusting for incident cardiovascular (CV) disease. Conclusions: In this population‐based cohort, variables obtained by CV imaging and biomarkers of inflammation, coagulation, atherosclerosis, myocardial injury and stress, and cardiac collagen turnover were associated with YAL, an important outcome that integrates physical ability and longevity in older persons.